2019
DOI: 10.1590/1679-78255326
|View full text |Cite
|
Sign up to set email alerts
|

Fragmentation model for the tensile response of unidirectional composites based on the critical number of fiber breaks and the correction of the fiber-matrix interfacial strength.

Abstract: A fragmentation model based on global load sharing (GLS) theory is developed to obtain stress-strain curves that describe the mechanical behavior of unidirectional composites. The model is named + * because it is based on the Critical Number of Breaks model (CNB) and on the correction of the fiber matrix interfacial strength, *. Model allows both obtaining the ultimate tensile strength of CFRP and GFRP composites, and correcting the vs curve to match its peak point with the predicted strength, which is more ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 53 publications
(51 reference statements)
0
6
0
1
Order By: Relevance
“…For the last fiber mixing ratio, α=0.75 (Figure 6h), ultimate tensile strength of CNB+τ* model is in the range of the other two models (FEM and FPM), but the ultimate strain is overpredicted. The CNB+τ* model was previously validated in [36] with experimental results for non-hybrid composites. In total, 25 experimental works were considered, obtaining an average relative difference of 5.01%.…”
Section: Comparison Of a Proposed Numerical Model With Previous Numerical Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…For the last fiber mixing ratio, α=0.75 (Figure 6h), ultimate tensile strength of CNB+τ* model is in the range of the other two models (FEM and FPM), but the ultimate strain is overpredicted. The CNB+τ* model was previously validated in [36] with experimental results for non-hybrid composites. In total, 25 experimental works were considered, obtaining an average relative difference of 5.01%.…”
Section: Comparison Of a Proposed Numerical Model With Previous Numerical Resultsmentioning
confidence: 99%
“…Given the advantage of GLS-based models to provide fast results, a model to accurately predict the ultimate tensile strength of unidirectional composites within a GLS framework, named CNB+τ* model, was previously developed [35], [36]. According to that model, the failure of the composite occurs when a critical density of fiber breaks, depending entirely on the constituent properties, is reached; when such happens, the fiber breaks interaction becomes significant to create 'avalanches events' of broken fibers that bring about the failure.…”
Section: Prediction Of Composite Tensile Behavior By Cnb+τ* Modelmentioning
confidence: 99%
See 2 more Smart Citations
“…However, GF-PP had the lowest GF content in comparison to CPW-PP and GF-CPW-PP. Previous studies reported that [30][31][32][33] composite failure mechanisms may be represented as follows: when there is no load disruption by the reinforcement break under mechanical testing, the load is uniformly distributed among the fibres next to the break fibre resulting in a degree of concentrated stress developing on those fibres and damaging the surrounding matrix. Therefore, the presence of intense moisture increased vulnerability and decreased the tensile strength of the composites.…”
Section: Morphologymentioning
confidence: 99%